A study of the association of compensations on employees satisfaction in the public sector in Egypt - El Tahawy, Mai (AUC Knowledge Fountain, 2020)
This paper demonstrates the correlation between compensations and employees’ satisfaction in the public sector. It tries to answer whether financial compensation is the most important factor in job satisfaction and determine the other factors attracting employees to work in the public sector job. The research objective attempts to provide an addition to the existing scholars through examining the Egyptian public sector as well as enhancing the validity and reliability of the existing research. This study is using quantitative data in order through collecting questionnaires to analyze which types of compensations affect employees’ satisfaction in the public sector. The research study used three tests to measure the correlation between job satisfaction and compensations. These are the Chi-square test, Spearman correlation, and Ordinal Logistics Regression. The results of the study reveal a correlation between the dependent variable which is job satisfaction and the independent variables which are income level, the satisfaction of take-home pay, work status, and steady employment, while the results rejected the impact of working hours and leave policies on job satisfaction.